Advances in Green Infrastructure Planning - Kim, Hyun-Woo (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
The expansion of urban areas has facilitated the conversion of undeveloped lands, which has led to environmental degradation, such as loss of habitats, hydro-modification, and the collapse of existing ecosystems. Recent climate change has exacerbated these damages by causing more frequent and serious hazards. To attenuate the impacts of urbanization and the negative effects of climate change, green infrastructure (GI) planning (e.g., nature-based strategies, technologies, policies, and solutions) has arisen as an important approach for balancing urban development and nature. GI offers a variety of benefits to our cities by reducing stormwater runoff, heat waves, and air pollution; expanding wildlife habitats; and increasing recreational opportunities and even nearby property values.